Intergroup Bias Among Jakarta's Road Users - Ariyanto, Amarina; Hafiyah, Nurlyta; Soesetio, Sri Rochani (Makara Human Behavior Studies in Asia, 2011)
The goal of this study is to examine intergroup bias among people who use roads in Jakarta. Intergroup bias refers to the tendency to prioritize, treat and perceive in-group members more favorable than out-groups. Three different groups of road users participated in this study: private drivers, motor riders, and public transportation drivers. Intergroup bias is measured as perception bias and attribution bias. The findings show that both forms of bias occur among the road users. Intergroup attribution bias that is found among the three groups are more in-group than out-group attribution bias. The private car drivers, motor riders, and public transportation drivers tend to attribute positive behavior of in-group to internal factor and negative behavior of in-group to external factors. Index of effect size in perception bias indicates substantive levels and represents large effect in the population.